Mimicking Neuroplasticity in a Hybrid Biopolymer Transistor by Dual Modes Modulation. (9th May 2019) - Lv, Ziyu; Chen, Meng; Qian, Fangsheng; Roy, Vellaisamy A. L.; Ye, Wenbin; She, Donghong; Wang, Yan; Xu, Zong‐Xiang; Zhou, Ye; Han, Su‐Ting
Abstract: Neuromorphic computing systems that are capable of parallel information storage and processing with high area and energy efficiencies, offer important opportunities for future storage systems and in‐memory computing. Here, it is shown that a carbon dots/silk protein (CDs/silk) blend can be used as a light‐tunable charge trapping medium to fabricate an electro‐photoactive transistor synapse. The synaptic device can be optically operated in volatile or nonvolatile modes, ensuring concomitant short‐term and long‐term neuroplasticity. The synaptic‐like behaviors are attributed to the photogating effect induced by trapped photogenerated electrons in the hybrid CDs/silk film which is confirmed with atomic force microscopy based electrical techniques. In addition, system‐level pattern recognition capability of the synaptic device is evaluated by a single‐layer perceptron model. The remote optical operation of neuromorphic architecture provides promising building blocks to complete bioinspired photonic computing paradigms. Abstract : An optoelectronic synaptic transistor based on a hybrid light‐tunable charge trapping medium is demonstrated. Optical programming and electrical erasing memory characteristics, along with volatile and nonvolatile memory are features of the synaptic device, enabling the mimicking of a range of neuroplasticity behaviors, including short‐term plasticity and long‐term potentiation.